The role of cycloferon in the treatment of chronic Helicobacter pyloriinduced gastritis with gastric erosions associated with Epstein – Barr virus - T. E. Afanasenkova; E. E. Dubskaya (Лечащий Врач)
Evaluation of the effectiveness of cycloferon when used in complex therapy and for the prevention of chronic Helicobacter pyloriinduced gastritis with gastric erosions associated with Epstein – Barr virus. The study included 105 patients with chronic Helicobacter pylori-induced gastritis with gastric erosions associated with the Epstein – Barr virus, divided into 2 groups: group 1 (65 patients) – patients who were prescribed the antiviral drug cycloferon in addition to anti-helicobacter therapy (12,5% 2,0 ml intramuscularly, the course of administration of the drug depended on the number of copies per 105 cells of the Epstein – Barr virus infiltrate); group 2 (40 control patients), who were prescribed only anti-helicobacter therapy. In each group, patients were distributed depending on the severity of the disease and the number of copies of Epstein – Barr virus per 105 infiltrate cells. The detection of Helicobacter pylori (H. pylori) was carried out by three methods: a rapid urease test based on the results of a Helpil test, a histological examination of smears taken from gastrobiopaths, and a PCR biopsy. To determine the number of Epstein – Barr virus copies per 105 infiltrate cells, the PCR method was used using reagent kits for detecting Epstein – Barr virus DNA in clinical material with real-time hybridization-fluorescence detection Amplisens Epstein – Barr virus-screen-FL. In patients with chronic Helicobacter pylori-induced gastritis with gastric erosions, the use of meglumine acridone acetate in antihelicobacter therapy reduces the severity of the disease and the frequency of exacerbations. Interferon inducers, in particular meglumine acridone acetate, belong to a new class of antiviral drugs. Possessing bifunctionality, meglumine acridone acetate combines a wide range of pharmacological effects, which makes it possible to use it as a therapeutic and prophylactic agent.